AN OPEN-SYSTEM RESPIROMETER FOR MEASURING STEADY-STATE OXYGEN UPTAKE BY AQUATIC ANIMALS APPLIED TO THE SCALLOPS Pecten Maximus L. - Djoko Suprapto (JOURNAL OF COASTAL DEVELOPMENT, 2002)
An open-system respirometer for measuring steady-state oxygen uptake rate of aquatic animals is described. The principle of the measurement was to calculate the difference between the oxygen concentrations of the water entering the respiratory chambers with that out from the respiratory chambers. This difference indicated the oxygen consumed by the animals for their respiration. The measuring system was tested to calculate the oxygen consumption related to dry body weight of scallop Pecten maximus L. collected from different populations. This correlation was  expressed by allometric equation as: Y = aXb. The equation was then discussed with the finding of several authors.